Visualisasi dan Analisis Sebaran Data Sekolah (SD, SMP dan SMA) di Kota Bengkulu Menggunakan Geocoding R - Dyah Rizky Alyudin; Parluhutan Manurung; Masita Dwi Mandini Manessa (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  Schools are a means of infrastructure needed to fulfill the law's educational obligations, so the distribution of schools needs to be a concern so that access to education for every citizen can be achieved. Analysis of school distribution is one way to see the needs of schools in an area through visualization of the distribution of school data in Indonesia, including Bengkulu City. However, access to school coordinates is limited, so a method is needed to obtain coordinate points for mapping and distribution analysis. Meanwhile, there is still little research regarding taking coordinate points from addresses for school data distribution in Indonesia, including Bengkulu City. Even though Geocoding with R is one way to get the coordinates of an address well. By using geocoding and visualization using the Google API, mapview, shiny and the ggplot function in R, we can show variations in the distribution of geocoding data so that distribution analysis can be carried out. The results of the visualization of the distribution of Bengkulu City school data look good, with the Muara Bangkahulu District lacking a high school, while Teluk Segara, Ratu Agung and Muara Bangkahulu lack a junior high school, and the Kampung Melayu and Sungai Serut Districts lack an elementary school. Visualizing the distribution of this data would be better done by combining four methods, namely Google API, mapview, shiny and ggplot because each method shows the advantages and disadvantages of the display.Abstrak: Sekolah menjadi suatu sarana prasarana yang diperlukan untuk memenuhi Undang-Undang dalam kewajiban pendidikan, sehingga sebaran sekolah perlu menjadi perhatian agar akses menerima pendidikan bagi setiap warga negara dapat terlaksana. Analisis sebaran sekolah menjadi salah satu cara untuk melihat kebutuhan sekolah di suatu wilayah melalui visualisasi sebaran data sekolah di Indonesia termasuk Kota Bengkulu. Akan tetapi, akses mengenai koordinat sekolah terbatas, sehingga diperlukan metode untuk mendapatkan titik koordinat untuk melakukan pemetaan dan analisis sebaran. Sementara itu, penelitian mengenai pengambilan titik koordinat dari alamat untuk sebaran data sekolah masih sedikit di Indonesia termasuk Kota Bengkulu. Padahal Geocoding dengan R adalah salah satu cara untuk mendapatkan koordinat dari suatu alamat dengan baik. Dengan menggunakan geocoding dan visualisasi menggunakan Google API, mapview, shiny dan fungsi ggplot di R, dapat memperlihatkan variasi sebaran data hasil geocoding sehingga analisis sebaran dapat dilakukan. Hasil visualisasi sebaran data sekolah Kota Bengkulu tampak baik dengan wilayah yang Kecamatan Muara Bangkahulu kekurangan SMA, sementara Teluk Segara, Ratu Agung dan Muara Bangkahulu kekurangan SMP, serta Kecamatan Kampung Melayu dan Sungai Serut kekurangan SD. Visualisasi sebaran data ini akan lebih baik dilakukan dengan mengkombinasikan dari empat metode yaitu Google API, mapview, shiny dan ggplot dikarenakan masing-masing metode menunjukkan kelebihan dan kekurangan tampilan.